A Meta‐Analysis of Fault Slip Rates Across the Central Apennines. Issue 1 (4th January 2022) - Carafa, M. M. C.; Di Naccio, D.; Di Lorenzo, C.; Kastelic, V.; Bird, P.
Abstract: Several methods such as paleoseismic trenching, mapping of offset geomorphic markers, and dating of scarp profiles have been used to determine slip rates of normal faults in the central Apennines. Combining measurements obtained with different methods remains challenging because non‐tectonic processes can introduce noise or spurious signals that are elusive to quantify, and these influence slip rate estimates. To this end, we meta‐analyzed throw measurements with associated ages collected in the central Apennines with several methods to quantify such erratic fluctuations and method‐related variances. We show that throw rates are overdispersed with respect to nominal uncertainties in throw and age; therefore, they are commonly affected by unmodeled noise processes. After comparing throw rate distributions sampling the same faults with different techniques, no clear spatio‐temporal patterns appear, but only quasi‐random noise. Assuming that field investigators sampled real tectonic features (i.e., fault scarps), we find that such erratic throw rates indicate total uncertainties are two to three times greater than the stated observation uncertainties. In this situation, a simple and robust null hypothesis is appropriate. We propose that most faults should be assumed to have uniform throw rate along their traces, except for possible tapering near unconnected ends. We also propose that models in which throw rates are time‐dependent (within the last 25 kyr) are not yet justified. Then, relying on the estimated total uncertainties, we determine the most probable long‐term fault throw rate for each active fault by combining different throw‐rate probability density functions. Plain Language Summary: Recent advances in paleoseismology are expected to provide crucial components for seismic hazard models in the years to come. Different paleoseismological methods sample complementary features along active fault traces. Thus, the most significant progress in seismic hazard analyses using paleoseismological data will stem from advanced statistical methods comparing (and connecting) outcomes of different techniques. However, comparing alternative techniques remains problematic, given the limited number of feature measurements across the same active fault. The available data for active faults across the central Apennines, collected with diverse methods by different research groups, represents an opportunity to solve this issue due to their dense concentration. Furthermore, such data richness motivated us to carefully investigate the spatial and temporal variabilities to discriminate tectonic signals from noise. We meta‐analyzed available throw measurements (and their ages), inspected for disagreements among features, and found evidence for significant data overdispersion. Hence, we argue that better quantification of the total uncertainties is needed and that uniform throw rate (along each trace and through the last 25 kyr of geologic time) is still the most reasonable model for many scientific and urban planning purposes. Key Points: We meta‐analyzed throw measurements for active normal faults in the central Apennines Throw rates are overdispersed with respect to age and offset uncertainties; therefore larger uncertainties are implied A robust null hypothesis is that faults have quasi‐constant throw rates through time and along trace except for tapering at unconnected ends